Pemberian Sanksi Tindak Pidana Penyebaran Berita Bohong Yang Mengakibatkan Keonaran Publik Dalam Sistem Hukum Di Indonesia - Lubis, Muhammad Ridwan (ARBITER: Jurnal Ilmiah Magister Hukum, 2023)
Inaccurate and factually incorrect reporting can lead to the dissemination of false information, resulting in public disorder. This occurrence raises concerns about the need for stringent criminal sanctions against perpetrators of spreading false news, especially in the context of online media. The term "hoax" is used to refer to false news or defamation with the potential to disturb public tranquility. Preventing the spread of false news in online media requires clear criminal sanctions, as stipulated in Article 28 paragraph (1) and Article 45A paragraph (1) of the Republic of Indonesia Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law). In the process of proving the criminal act of spreading false news online, Article 5 of the ITE Law introduces a new form of evidence, namely Electronic Information and Electronic Documents along with their printouts. This strengthens the legal framework for addressing the electronic dissemination of false news. This research aims to investigate the criminal provisions against perpetrators of spreading false news and their impact on society.